A Note on the Exponential G-Martingale - Yunsheng Lu; Yingying Liu (Abstract and Applied Analysis)
We get the exponential G-martingale theorem with the Kazamaki condition and tell a distinct difference between the Kazamaki’s and Novikov’s criteria with an example.